A divulgação científica a partir das histórias em quadrinhos para o ensino de Ciências no 6º ano - Carvalho, Francinete Bandeira (2020)
Discussing Scientific Dissemination - DC is also talking about resources that favor it at school, therefore, Comic Books - Comics with scientific information are important allies for the teaching and learning process of students. Our problematization is in the sense of discovering how Scientific Dissemination in the 6th year of Elementary School can be carried out from the comic books? The general objective of this research was: To understand how Scientific Dissemination in the 6th year of elementary school can be carried out from comic books. The specifics were: a) Find out if Comics have been worked on in the classroom for science teaching, b) Investigate who students in the 6th year of elementary school identify as science disseminators, c) Analyze whether the stories in comics from the school library of the researched institution has the potential to support the scientific dissemination process in the school. The research methodology is identified with qualitative research, through a phenomenological approach since, in addition to describing the subject's sense and experience, it is important to interpret the phenomenon in the light of theorists. The research was of a participatory nature, where the researcher immersed himself in the context of the subjects to better understand their reality. It was held at a state school in the public school system, with a 6th grade teacher and her class, 11 (eleven) year old students. Together with the teacher, an unstructured interview was used, and with the students, a round of conversation to find out if the students liked comics and if they understood their relationship with Science; As well as a workshop on comics aiming to involve students to feel like disseminators of Science. We perceive the importance of the teacher's role in relation to DC, as he is the one who will be the mediator, using the comics with scientific content to work the Teaching of Science and thus, provide a more significant teaching and learning process for children. Keywords: Scientific Dissemination. Comics. Science teaching.